Penerapan model pembelajaran SQ3R untuk meningkatkan keterampilan membaca pemahaman peserta didik kelas IV sekolah dasar - Amalia, Rinda Suci (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The purpose of this research is improving reading comprehension skills problems by applying SQ3R model. This research has two cycles in Classroom Action Research. The students of the 4th students at SDN Pajang IV Surakarta in the 2019/2020 academic year are the subjects, totalling 26 students. Data collection techniques in this research are interviews, observation, test, and documentation. Data analysis in kuantitative used content validity and triangulation. Qualitative analysis data using the Miles-Huberman interactive model. Research result in the first cycle in a percentage of 53.84% in classical, and the research continued with the second cycle and the result are in percentage are 88.46% in classical. Based on the result of the research, it can be conclude that reading comprehension skill on 4th students of SDN Pajang IV Surakarta in the 2019/2020 academic year can be improved through the SQ3R model.